Bacterial microbiome of Rhipicephalus sanguineus ticks collected from dogs in the Mnisi community, South Africa - Oosthuizen, Marinda C. (University of Pretoria, 2020)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2019.